2023
DOI: 10.3390/fishes8020111
|View full text |Cite
|
Sign up to set email alerts
|

Fish Viscera Silage: Production, Characterization, and Digestibility of Nutrients and Energy for Tambaqui Juveniles

Abstract: Fish viscera can be an important source of protein and energy for aquafeed, and its use contributes to circular aquaculture. The aim of this study was to produce acid and fermented silage from fish viscera to determine their nutritional value and the apparent digestibility coefficient of nutrients and energy for juvenile tambaqui (Colossoma macropomum). An acid silage and three fermented silages with different sources of carbohydrates (molasses, wheat bran, and cassava waste) were produced with 0.25% sorbic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(36 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…Regarding the FAA profile ( Table 3 ), the total percentage of Gln and Tyr fell while Glu, Leu and Lys were the most prevalent during the silage, in the case of glutamic acid finishing day 10 at 10.3 ± 0.3 % of the total FAA. The profile was similar to the one reported by Santana et al (2023) [ 31 ], where a 7-day acid silage of tambaqui viscera was carried out. Analysis of variance showed that there was a significant difference between days of silage in terms of the amino acid profile.…”
Section: Resultssupporting
confidence: 87%
“…Regarding the FAA profile ( Table 3 ), the total percentage of Gln and Tyr fell while Glu, Leu and Lys were the most prevalent during the silage, in the case of glutamic acid finishing day 10 at 10.3 ± 0.3 % of the total FAA. The profile was similar to the one reported by Santana et al (2023) [ 31 ], where a 7-day acid silage of tambaqui viscera was carried out. Analysis of variance showed that there was a significant difference between days of silage in terms of the amino acid profile.…”
Section: Resultssupporting
confidence: 87%
“…Livestock and poultry processing by-products refer to the by-products produced during the slaughtering and processing of livestock and poultry, usually including bones, internal organs, fur, blood, and feathers [ 47 , 48 ]. These by-products are rich in nutrients and can be used to make various types of feed, providing comprehensive nutritional support for the animals.…”
Section: Types and Applications Of Unconventional Feedmentioning
confidence: 99%
“…Because small peptides and free amino acids can be absorbed more easily than intact proteins and do not require prior digestion by pancreatic proteases, fish silage may be more digestible than fishmeal, as suggested by several studies [34,35]. Santana et al [35] reported that fish viscera can be converted into both acid and fermented silage, which is a well-digested energy ingredient for aquafeed due to the high fat (around 60%) content in dry matter.…”
Section: Ensiling Technology: a Brief Overviewmentioning
confidence: 99%
“…Because small peptides and free amino acids can be absorbed more easily than intact proteins and do not require prior digestion by pancreatic proteases, fish silage may be more digestible than fishmeal, as suggested by several studies [34,35]. Santana et al [35] reported that fish viscera can be converted into both acid and fermented silage, which is a well-digested energy ingredient for aquafeed due to the high fat (around 60%) content in dry matter. The fermented silages produced with different sources of carbohydrates, such as molasses, wheat bran, and cassava waste, had a high protein content of 12% in terms of dry matter and were rich in essential amino acids, eicosapentaenoic acid (EPA), and docosahexaenoic acid (DHA), along with beneficial microorganisms.…”
Section: Ensiling Technology: a Brief Overviewmentioning
confidence: 99%